PENERAPAN METODE MIND MAPPING DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PENGANTAR EKONOMI BISNIS DI SMK NEGERI 1 KARANGANYAR TAHUN AJARAN 2014/2015 - Dwi Safrudin; Sunarto Sunarto; Sudarno Sudarno (Department of Economics Education, Universitas Sebelas Maret, 2018)
The purpose of this research is to improve the learning outcomes of students of class X Marketing 2 SMK Negeri 1 Karanganyar on subjects Introduction to Business Economics academic year 2014/2015 through the application of the Mind Mapping method with the scientific approach. This type of research is a classroom action research. The subjects were students of class X Marketing 2 SMK Negeri 1 Karanganyar in the school year 2014/2015 totaling 36 learners. Source data comes from teachers and learners. Data collection techniques were used (a) observation, (b) interview, (c) documentation (d) test. Test the validity of the data used triangulation techniques and sources. Analysis of the data is used descriptive comparative statistical analysis. Research procedure includes the step (a) planning, (b) measures, (c) observation, (d) reflection.Based on the result of this research, in the first cycle learning outcomes of students has increased as much as 1.55 (average value 74.64 pre-cycle and average value of the first cycle 76.19) and the percentage of completeness increased 30.55% (percentage of pre-cycle 44.45% and 75% the first cycle). In the second cycle learning outcomes of students has increased as much as 1.32 (the average value of the first cycle of 76.19 and the average value of the second cycle 77.51) and the percentage of completeness increased 2.78% (the percentage of first cycle and cycle 75% II 77.78%). The conclusions of this research is the application of the Mind Mapping method with the scientific approach can improve the learning outcomes of students of Class X Marketing 2 SMK Negeri 1 Karanganyar in the school year 2014/2015 on subjects Introduction to Business Economics.